The Role of Empathy and Emotional Labor as Predictors of Burnout Syndrome in Brazilian Oncologists - Romeiro, Fernanda B. (2025)
Background: Among medical specialties, oncologists have been consistently identified as a group with heightened risk for Burnout Syndrome. Objective: The present study aimed to identify the frequency and predictive power of emotional labor and physician empathy for Burnout Syndrome in medical oncologists. Method: In a cross-sectional design, 128 physicians with 10 years of experience on average answered an online survey, including the Spanish Burnout Inventory (assessing enthusiasm towards the job, psychological exhaustion, indolence, and guilt), the Emotional Demand scale from the Questionnaire on the Experience and Assessment of Work, the Emotional Dissonance taken from the Frankfurt Emotion Work Scales, and the Jefferson Empathy Scale - Physician Version (assessing perspective-taking, compassionate care, and the ability to put oneself in the patient's place). Result: Higher Burnout Syndrome scores were observed for enthusiasm towards the job subscale of the Spanish Burnout Inventory, which can also represent a lack of enthusiasm towards the job, followed by psychological exhaustion. About half of the participants showed critical levels of illness, which can lead to serious problems in the quality of work and a high risk of absence due to related health issues. Overall, Burnout Syndrome was best predicted by higher levels of emotional demand, while some dimensions were also predicted by emotional dissonance and empathy. Conclusion: Empathy was best associated with preventive levels of Burnout Syndrome and benefits the physician-patient relationship, which is related to increasing patients' satisfaction and appreciation of physicians who are sensitive to their emotional demands.